2018
DOI: 10.1002/cncr.31239
|View full text |Cite
|
Sign up to set email alerts
|

Lymphedema in ovarian cancer survivors: Assessing diagnostic methods and the effects of physical activity

Abstract: With a potential prevalence of LLL as high as 40%, further evaluation of diagnostic methods is required to better characterize this side effect of ovarian cancer treatment. No adverse effect of exercise on LLL was found. Further research is strongly needed to evaluate predictors of LLL and the effects of exercise on LLL in order to develop effective physical activity recommendations for women with ovarian cancer. Cancer 2018;124:1929-37. © 2018 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 27 publications
0
20
1
3
Order By: Relevance
“…However, research examining the PA role in subjects with LLL secondary to cancer treatment is scant [18]. Only a few studies reported the occurrence of adverse effects due to the practice of physical exercise, though a possible benefit to the affected lower limb is not yet well established [18,23]. In this context, a study has evaluated the effect of an eight-week supervised progressive weight training, followed by three months unsupervised, on leg swelling and functional mobility as well as QoL in subjects with secondary LLL [18].…”
Section: Discussionmentioning
confidence: 99%
“…However, research examining the PA role in subjects with LLL secondary to cancer treatment is scant [18]. Only a few studies reported the occurrence of adverse effects due to the practice of physical exercise, though a possible benefit to the affected lower limb is not yet well established [18,23]. In this context, a study has evaluated the effect of an eight-week supervised progressive weight training, followed by three months unsupervised, on leg swelling and functional mobility as well as QoL in subjects with secondary LLL [18].…”
Section: Discussionmentioning
confidence: 99%
“…Outcomes evaluated in trials have also broadened. There is now trial evidence (again of varying strength) regarding the potential positive effect of exercise for more contemporary treatmentrelated side effects, such as chemotherapy-induced peripheral neuropathy, 18 myalgia and arthralgias, 19,20 lymphoedema (upper-and lower-limb), 21,22 bone health, 23-25 sarcopenia 26,27 and metabolic syndrome, 28 sleep quality, 29 cachexia, 30 cognitive impairment 31 and cardiotoxicity, 32,33 as well as outcomes particularly relevant to the clinical and public health setting, such as treatment adherence or completion [34][35][36] and cost-effectiveness. 37 In the past five years, preliminary findings have also become available from phase 2 exploratory studies that have reported the effect of exercise on survival outcomes.…”
Section: Evidence Of Exercise Benefit Following a Cancer Diagnosismentioning
confidence: 99%
“…There is scant research that has determined the level of physical activity in LLL patients during the treatment of cancer [ 15 , 57 ].…”
Section: Discussionmentioning
confidence: 99%